Household spending out of a tax rebate: Italian " exteuro80 tax bonus" - Andrea Neri; Concetta Rondinelli; Filippo Scoccianti (European Central Bank (ECB), 2017)
We estimate the consumption response of Italian households to the "Euro80 tax bonus" intro-duced in 2014, using the panel component on the Survey of Household Income and Wealth. We find that households that received the tax rebate increased their monthly consumption of food and means of transportation by about Euro20 and Euro30, respectively, about 50-60 per cent of the total bonus. There was a larger increase for households with low liquid wealth or low income. Our estimates are quite robust to different model specifications and are broadly in line with the evidence available from similar tax rebates in other countries but, due to the small sample size, are not always statistically significant. To understand the mechanism behind our results we then simulate an overlapping generations model of household consumption: the marginal propensity to consume generated by the structural model is in line with our empirical estimates.
Keywords: D12; E21; 330; fiscal stimulus; expenditure; consumer behavior